Motivational Factors in Continuing Education an Academic Achievement of Adult Learners (Malaysian Journal of Learning and Instruction, 2013)
Purpose â€“ The purpose of this study is to examine the relationship between motivational factors in continuing education and academic achievement of adult learners. The study is conducted due to a lack of research pertaining to academic achievement among adult learners particularly in Malaysia. Methodology â€“ A random sample of 150 part-time adult learners from a public university in Kota Kinabalu, Sabah, represented 202 part-time adult learners in the areas of social sciences and humanities at the university. A thirty-item questionnaire, adapted from Boshierâ€™s Education Participation Scale(EPS) (1991) and Neillâ€™s The University Students Motivation and Satisfaction Questionnaire 2 (TUSMSQ2) (2004) was used to examine their motivational factors i.e. personal development, career advancement, social pressure, social and communication improvement, and escapism. Self-reported cumulative grade point average (CGPA) was utilized as the measurement of academic achievement. Rasch analysis reaffirmed the content validity of items in the questionnaire. Findings â€“ The findings indicate that personal development and social pressure are the best predictors of academic achievement among adult learners. The motivational factors that are not significant as predictors are career advancement, social and communication improvement, and escapism. Adult learners with higher motivation for personal development (intrinsic motivation) perform better academically. Conversely, adult learners with higher motivation based on social pressure (extrinsic motivation) perform lower academically. Intrinsic motivation seems to be more powerful in enhancing academic achievement of adult learners as compared to extrinsic motivation. Significance â€“ This finding is crucial for program planners and adult educators. They will be able to lead adult learners to be more intrinsically motivated in continuing education. In this way, they will optimize their learning outcomes and develop quality human capital in Malaysia.